TEACHING VOCABULARY ABOUT WILD ANIMALS BY USING PHOTOS - Asnawi, .; ., Sudarsono; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of the research is to find out the effectiveness of teaching vocabulary by using photos. Based on the researcher observation in SMP Negeri 3 Simpang Hilir, most of students have problems in developing their vocabulary. In this case, needs to motivate students and develop thier enthusiam to learn English and creats a new atmosphere in the classroom bu using suitable technique to increase their vocabulary. The research hypothesis was whether the effective of the treatment was low, moderate, and high. The research method is pre-expremental, involving a group sample of class VIII A numbering 31 students. The data ware collected by multiple choice test. The data were analyzed by Effect Size Formula. The finding showedthat the studentsâ€™ score of pre-test is 606 and afterÂ the treatment, the studentsâ€™ score of post-test is 198. Therefore, the finding also showed that the score of effect size (ESvalue = 0,93 ishigher than the effect size (EStable = 0,8) of the treatment was categoried as â€œhighâ€. In conclusion in this experement of teaching vocabulary using photos is effective tolead students feel more interesting and enjoy studying English. Keywords: vocabulary, wild animals, using photos Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui efektivitas pengajaran kosakata dengan menggunakan foto. Berdasarkan pengamatan peneliti di SMP Negeri 3 Simpang Hilir, sebagian besar siswa memiliki masalah dalam mengembangkan kosakata mereka. Dalam hal ini, dirasakan perlu untuk memotivasi siswa dan mengembangkan antusiasme mereka untuk belajar bahasa Inggris dan menciptakan suasana baru di kelas menggunakan teknik yang sesuai untuk meningkatkan kosa kata mereka. Hipotesis penelitian adalah apakah efektivitas treatment itu rendah, sedang, atau tinggi. Metode penelitian yang digunakan pra-expremental, yang melibatkan sampel kelompok kelas VIII A berjumlah 31 siswa. Data dikumpulkan lewat beberapa tes pilihan ganda. Data dianalisis dengan Effect Size Formula. Temuan menunjukkan bahwa skor siswa saat pre-test adalah 606 dan setelah treatment, skor siswa saat post-test adalah 198. Oleh karena itu, temuan ini menunjukkan bahwa nilai besarnya efek ESvalue = 0,93 lebih besar dari besaran efek EStable = 0,8. Maka treatment ini dikategorikan sebagai